An Adlerian Reading of Masculine Protest in Donoghue’s Room - Mehrnaz Khoshgam; Bojan Zokaei; Fatemeh Kargar Bardaskan (Britain International for Academic Research (BIAR-Publisher), 2023)
The aim of the current paper is to unveil how masculine protest, courage and lifestyle for individuation process encouraged the characters to develop their personality through the novel and the way the characters resolve the personality problems in Donoghue’s Room which respectively are elaborated. The main focus of this study is on Adler Psychoanalysis. It's a dynamic challenge to know human behavior needs valuable insight. Thus, it's not surprising that the subject of personality and related human aspects has been explored by several theorists. Adler is among the authors who shared their perspectives on personality. Emma Donoghue uses Jack, a five years old boy, because the narrator within the novel Room. The novel also expounds the conflicts experienced by main character Ma. The novel elaborates when she leaves Room and meets new people, she progressively changes her personality. Ma begins to possess difficulty managing her emotions and is definitely enraged by others who treat her as if she is ill. She subsequently becomes despondent which causes her to become unpleasant, making her son the target of her wrath. Therefore, the novel explores Ma`s internal conflicts. Ma, the feminine protagonist, is at the middle of the story's internal conflict. The struggle between Ma and Ma's sense of oppression is that the female protagonist's internal conflict.